EFEKTIFITAS MODEL PEMBELAJARAN TRI KAYA PARISUDHA TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI SISWA KELAS IV SD GUGUS III KECAMATAN JEMBRANA TAHUN PELAJARAN 2019/2020 - Parwati Dewi Jatiningtyas (Guna Widya: Jurnal Pendidikan Hindu, 2020)
This study aims to determine the differences in Hindu and religious education learning outcomes between groups of students who are taught with the Tri Kaya Parisudha Rich learning model and groups of students who are taught with conventional learning models in class IV elementary students in Cluster III Jembrana District 2019/2020 Academic Year. This type of research is a quasi-experimental study with a non-equivalent posttest only controls group design. The population of this research is class IV elementary school students in Cluster III Jembrana Subdistrict 2019/2020 Academic Year, amounting to 148 people. Sampling using simple random sampling technique by lottery. The research sample is students in grade IV SD Negeri 1 Dauhwaru and students in grade IV SD Negeri 6 Dauhwaru. Data on learning outcomes of Hindu religious education and character were collected using a description test. The data obtained were analyzed using descriptive statistics and inferential statistics, namely the t-test. T-test analysis results obtained t is greater than t table (tcalculated 22.5> t table 2.021) this means that there are significant differences in learning outcomes of Hindu religious education and manners between groups of students who are taught with the Tri Rich Parisudha learning model and groups of students who are taught with conventional learning models. The findings obtained in this study are groups of students who follow learning using the Tri Rich Parisudha model, students look persistent and analytical to be able to look for problem-solving. Besides that, students also have the freedom and freedom to develop their creativity and critical thinking skills, so that the results of Hindu and religious education learning increase and students become more optimal. This means that the learning model of Tri Kaya Parisudha has a positive effect on the learning outcomes of Hindu religious education and character class IV students in Cluster III Jembrana District, Academic Year 2019/2020.